2016
DOI: 10.1002/psc.2852
|View full text |Cite
|
Sign up to set email alerts
|

First total synthesis of WLIP: on the importance of correct protecting group choice

Abstract: Cyclic lipodepsipeptides (CLPs) are a group of metabolites produced by Pseudomonas bacteria, involved in various biological functions and displaying a wide range of properties, including antibacterial and antifungal activities. The white line-inducing principle (WLIP) is a member of the viscosin group featuring a Glu2 amino acid. Recently, a total synthesis of pseudodesmin A - the Gln2 counterpart of WLIP - was described, and we here expand this route to Glu2 containing CLPs. We report the first total synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…While most other positions show complete conservation or conservative variations (Figure 1B), position 2 either features a negatively charged D-Glu, like in WLIP(D − ) or a neutral D-Gln as in PsdA (D 0 ). We previously showed (Geudens et al, 2017) that the activity of natural WLIP(D − ) is attenuated compared to natural PsdA(D 0 ), a result which could be reproduced here with synthetic WLIP (11) (De Vleeschouwer et al, 2016) which was not assayed before. It would therefore appear that the presence of an uncharged but polar sidechain amide is a trait that confers increased activity against a majority of strains, as compared to a negatively charged or apolar side-chain, respectively.…”
Section: General Considerationssupporting
confidence: 72%
See 1 more Smart Citation
“…While most other positions show complete conservation or conservative variations (Figure 1B), position 2 either features a negatively charged D-Glu, like in WLIP(D − ) or a neutral D-Gln as in PsdA (D 0 ). We previously showed (Geudens et al, 2017) that the activity of natural WLIP(D − ) is attenuated compared to natural PsdA(D 0 ), a result which could be reproduced here with synthetic WLIP (11) (De Vleeschouwer et al, 2016) which was not assayed before. It would therefore appear that the presence of an uncharged but polar sidechain amide is a trait that confers increased activity against a majority of strains, as compared to a negatively charged or apolar side-chain, respectively.…”
Section: General Considerationssupporting
confidence: 72%
“…In this heat map, MIC 1/2 values identical to the reference are indicated in green, as are relative changes by a factor of 0.5 or 2 since CLSI guidelines state that a difference in MIC 1/2 value corresponding to one twofold dilution should not be considered as a relevant difference (Clinical and laboratory standards Institute [CLSI], 2012). This was the case for the activity of the synthetic versions of WLIP (11) (De Vleeschouwer et al, 2016), PsdA , and (22) viscosinamide (data not shown) when compared to their natural counterpart. Significant reductions in activity are colorcoded starting from a factor of 4, coded in yellow, followed by a factor of 8 in orange, while any change in relative MIC 1/2 value by a factor equal to or larger than 16 is coded in red.…”
Section: General Considerationsmentioning
confidence: 79%
“…In all cases, a separate analysis should be performed to elucidate the stereochemistry of the 3-hydroxy fatty acid moiety (57). Here, we rather build on our previously developed total chemical synthesis route for Viscosin (9:7) group CLiPs (47, 58) to synthesize the three remaining (8:6)-Lx (x=1, 4, 5) sequences (Table 1). The total chemical synthesis strategy mostly relies on solid phase peptide synthesis, affording considerable automation and rapid access to multiple homologous sequences through parallel synthesis (47, 58, 59).…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate that P. poae FL10F produces an extracellular compound active against E. amylovora S435 that can be attributed to white-line-inducing principle (WLIP), a lipodepsipeptide belonging to the viscosin subfamily, which includes massetolides E, F, L, and viscosin. WLIP a member of the viscosin group of cyclic lipononadepsipeptides featuring a Glu2 amino acid with both antifungal as well as antibacterial activity (against gram-positive bacteria) (De Vleeschouwer et al, 2016;Lo Cantore et al, 2006). In addition to linking the known phenotypes of white line production and hemolytic activity of a WLIP producer with WLIP biosynthesis, additional properties of ecological relevance conferred by WLIP production were published, namely, antagonism against Xanthomonas as well as involvement in swarming and biofilm formation (Rokni-Zadeh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%